Konsumsi lemak total, lemak jenuh, dan kolesterol sebagai faktor risiko sindroma metabolik pada masyarakat perkotaan di Denpasar - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
ABSTRACT Background: Metabolic syndrome is a health problem with its increasing prevalence. It is characterized by a group of metabolic risk factors including abdominal obesity, dyslipidemia, elevated blood pressure and insulin resistance. Metabolic syndrome affected by changes in lifestyle and unhealthy dietary patterns with high cholesterol, saturated fatty acid and trans fatty acid. Objective: The study was conducted to analyze the relationship between fat consumption with metabolic syndrome among adult people in Denpasar city. Method: The case control study designed was applied. The cases were adult people who had metabolic syndrome, and the control was healthy people from the case-neighboring household. Total subject were 130, taken by consecutive sampling: 65 cases and 65 controls. The subjects identity, fat intake, waist circumference, blood pressure and fasting blood sugar were collected. The food frequency questionnaire (FFQ) was used to measure fat consumption and blood glucose test meter for measuring fasting blood sugar. Mantel Haenzel statistic analysis were used to test the association of fat intake with metabolic syndrome. Result: The study showed that means of metabolic syndrome components in case group was higher than control (p 300 mg/day, and 90.8% had SAFA intake > 10%. Odd Ratio Mantel Haenzel analysis showed that fat consumption (fat total, cholesterol and frequency consumption of fat were risk factors to metabolic syndrome (OR >1)). Conclusion: There was significant relationship between fat consumption (fat total cholesterol, SAFA, frequency of fat consumption) and metabolic syndrome among adult people in Denpasar City. KEY WORDS fat consumption, metabolic syndrome